Localization of Wnt1 and Frizzled 2 and identification of their ligand-receptor relationship in the ovary tissue of immature mice - PANG Xun-sheng; LIN Chun-lian; XU Xue-ping; WANG Zheng-chao (浙江大学学报. 农业与生命科学版, 2011)
In order to reveal the mechanism of Wnt1 and Frizzled (Fzd) 2 in the regulation of ovarian and follicular development, twelve 3-week old mice were used to investigate the localization of Wnt 1 and Fzd2 in the ovary by immunohistochemistry (IHC) and their ligand-receptor relationship by co-immunoprecipitation (Co-IP). The results showed that a strong immunostaining of Wnt1 was found in the cytoplasm and on the member of oocytes of health primary and secondary follicles, as well as that in the granular cells near basal lamina of preantral and antral follicles, however Fzd2 staining was found only in the cytoplasm. There was weakly immunostaining of Wnt1 in granular cells around antrum and cumulus oophorus around zona pellucida. The elongated stromal cells round developing follicles or branched from ovarian cores were immunostained by Wnt1 and Fzd2. Furthermore, some scattered cells were also immunostained in the interstitial gland, while in the oocytes of follicular atresia, a strong and asymmetrical immunostaining was also found. Co-IP analysis showed that there was a direct interaction between Fzd2 and Wnt1 in the ovarian oocytes. Together, the results over clearly demonstrated the expression and localization of Wnt1 and Fzd2 in a cell-specific manner and their ligand-receptor relation, implying the important roles during ovarian follicular development.